2020
DOI: 10.1126/science.abb9772
|View full text |Cite
|
Sign up to set email alerts
|

A transmissible cancer shifts from emergence to endemism in Tasmanian devils

Abstract: Emerging infectious diseases pose one of the greatest threats to human health and biodiversity. Phylodynamics is often used to infer epidemiological parameters essential for guiding intervention strategies for human viruses such as severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2). Here, we applied phylodynamics to elucidate the epidemiological dynamics of Tasmanian devil facial tumor disease (DFTD), a fatal, transmissible cancer with a genome thousands of times larger than that of any virus. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(90 citation statements)
references
References 63 publications
4
83
0
1
Order By: Relevance
“…We also found neoplastic mussels without genetic chimerism suggesting the presence of conventional non-transmissible cancers.The analysis of the genotype of 6 tumors from M. edulis hosts confirmed the M. trossulus origin of MtrBTN2 but with an excess of M. edulis-state SNP alleles compared to MtrBTN1 and the M. trossulus population we analysed, or a deficit compared to the highly introgressed M. trossulus population of the Baltic Sea. We surprisingly observed a high amount of nuclear and mitochondrial polymorphism in MtrBTN2 samples which defines two sub-lineages that co-exist and spread in the same populations, as it has been observed in other transmissible cancers(CTVT : Baez-Ortega et al 2019, DFTD: Kwon et al 2020, Patton et al 2020.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…We also found neoplastic mussels without genetic chimerism suggesting the presence of conventional non-transmissible cancers.The analysis of the genotype of 6 tumors from M. edulis hosts confirmed the M. trossulus origin of MtrBTN2 but with an excess of M. edulis-state SNP alleles compared to MtrBTN1 and the M. trossulus population we analysed, or a deficit compared to the highly introgressed M. trossulus population of the Baltic Sea. We surprisingly observed a high amount of nuclear and mitochondrial polymorphism in MtrBTN2 samples which defines two sub-lineages that co-exist and spread in the same populations, as it has been observed in other transmissible cancers(CTVT : Baez-Ortega et al 2019, DFTD: Kwon et al 2020, Patton et al 2020.…”
supporting
confidence: 66%
“…In Tasmanian devils two independent transmissible cancers lineages have emerged in the last 30 years. In bother cases, although at different spatiotemporal scales, genome studies have shown early diversification into sublineages and secondary co-existence of some divergent sublineages (Baez-Ortega et al 2019, Kwon et al 2020Patton et al 2020). Studies in marine bivalves also showed multiple emergences (two in Cerastoderma edule, Metzger et al 2016 and two in Mytilus trossulus, Yonemitsu et al 2019) and for the first time in transmissible cancer research, transmissions crossing the species barrier (BTN lineage in Polititapes aureus has a Venerupis corrugata origin, Metzger et al 2016, and MtrBTN2 in M. edulis and M. chilensis has a M. trossulus origin, Yonemitsu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We surprisingly observed a high amount of nuclear and mitochondrial polymorphism in MtrBTN2 samples. This polymorphism defines two sublineages that co-exist and spread in the same populations, as it has been observed in other transmissible cancers (CTVT: Baez-Ortega et al 2019, DFTD: Kwon et al 2020, Patton et al 2020.…”
Section: Discussionmentioning
confidence: 73%
“…If DFTD persists long-term in the devil population with ongoing coevolution, it may lead to diversifying selection for specific, qualitative host resistance mechanisms [83]. Indeed, phylodynamic analysis of DFTD as it spread across Tasmania supports the hypothesis that devils may be mounting a response; transmission rates have decayed such that DFTD appears to be shifting from emergence to endemism [85]. Although host-genomic variation was not jointly considered in that study, the combined evidence of multiple studies demonstrating rapid evolutionary response of devils to DFTD, including this one, support these interpretations.…”
Section: (C) Comparing Contemporary and Historical Time Scalesmentioning
confidence: 94%
“…The widespread contemporary evolution we found in devils reflects the recent prediction [83] that response to an emergent disease is most likely to be controlled by many genes conferring quantitative resistance [84], for example, by reducing the within-host growth rate of tumours. DFTD is predicted to become less virulent in the short-term [31,85]. If DFTD persists long-term in the devil population with ongoing coevolution, it may lead to diversifying selection for specific, qualitative host resistance mechanisms [83].…”
Section: (C) Comparing Contemporary and Historical Time Scalesmentioning
confidence: 99%